Efeito do método de síntese na microestrutura e propriedades elétricas de céria-cálcia - Garcia, Maxwell Ferreira de Lima Garcia (2019)
The growing search for clean energy technologies has led to the discovery of new sources of sustainable energy. This research aimed to study the effect of the route of synthesis on the microstructure and the electrical properties of an electrolyte material for the electrochemical conversion of energy to solid oxide fuel cells. A sol-gel protein method and the solid state reaction route preceded by high-energy grinding of a stoichiometric mixture of CeO2 + calcium carbonate (from shellfish powder) were used to synthesize citric-calcium electrolytes from composition (Ce0.9Ca0.1O1.95). The results of X-ray diffractometry confirm the obtainment of solid solution, free of secondary phases, in powders and sintered samples. Doping with 10 mol% of calcium gave relative densities above 95% at sintering temperatures from 1300 °C. The microstructural characterization by STEM allowed to investigate the average grain size and the residual porosity. Samples obtained by the sol-gel method show higher grain boundary conductivity due to lower dopant segregation. The electrical properties were analyzed by impedance spectroscopy in air atmosphere. The total conductivity reaches 8x10-3 S.cm-1 (sol-gel protein method) and 1,3x10-3 S.cm-1 (solid state reaction) at 600 °C for samples sintered at 1450 °C. These values are close to those reported in the literature for ceramics of the same composition obtained by other synthesis routes.